Motorways in Britain today and tomorrow : proceedings of the conference organized by the Institution of Civil Engineers in London, 26-28 April 1971 - Davis, Joyce (Institution of Civil Engineers, 1971)
Papers cover topics such as motorway administration, motorway planning, motorway experience in counties, the consulting engineer's view, user aspects, trends in research on motorway design and use, and more.